Nardo, Ed., The Great Depression - Woestman, Kelly (Teaching History: A Journal of Methods, 2003)
The Great Depression, part of the Turning Points of World History series published by Greenhaven Press, suffers from several glaring weaknesses despite its inclusion of essays by notable New Deal historians and some usable primary source documents. The major weakness is that, in spite of being part of a series on World History, it focuses solely on the United States. One current goal of historical literacy is to help students understand the broader global context of events and, based on this criterion, the book fails.